Making consistent judgements: Assessing student attainment of systematic achievement targets - Bolt, Susan (Routledge Inform Ltd, 2011)
Making Consistent Judgments (MCJ) was a systemic professional development program designed to increase teachers' capacity to make consistent judgments about students' achievement of educational standards in government schools in Western Australia; the MCJ program was in operation from 2004 to 2007 (Department of Education and Training 2007; 2008). The author describes the MCJ program as a case study in the context of the educational environment in which it was implemented and evaluated. Data were collected as a result of participant observation, documentation, and artefacts. Examples are drawn from the English learning area.